Evaluasi Karakteristik Roti Komposit Bebas Gluten dengan Konsentrasi Hidrokoloid dan Waktu Proofing yang Berbeda - Indahsari, Irawati Nur; Sutrisno, Aji; Ulandari, Devy (Universitas Bumigora, 2024)
Bread is generally made from wheat flour which contains gluten is known to have a negative effect on celiac disease patients, so other alternative ingredients are needed in making gluten-free bread. However, the use of these ingredients has a weakness in ability to retain gas during the proofing process, so a hydrocolloid additive, namely Carboxy methyl cellulose (CMC). The aim of this research is to determine the effect of adding CMC and proofing time on the physical characteristics of gluten-free bread. The research method used was a factorial randomized block design (RBD). Factors used in this research was the CMC concentration (1%, 2%, 3%) and the proofing time (30 and 45 minutes). A total of 6 treatment combinations were repeated 3 times to obtain a total of 18 experimental units. Data analysis took the form of analysis of variance (ANOVA) and further DMRT/BNT tests. The results showed that the addition of CMC and proofing time had a significant effect (p¡0.05) on physical characteristics such as volume development, hardness, and stalling rate. This study shows that the addition of CMC and the right proofing time can improve the physical characteristics of gluten-free white bread This research contributes to finding alternative products for people with celiac disease to get white bread products with good physical qualities.